The influence of love of money, locus of control and self-efficacy on the ethical decisions of tax consultants at the Surabaya branch of the Indonesian tax consultants association - Anggita Ninin Triyanti Triyanti; Aloisius Hama (Junal Ilmu Manajemen, 2023)
The purpose of this study was to determine the effect of love of money, locus of control and self efficacy on the ethical decisions of tax consultants. The population in this study were all tax consultants in Surabaya who were registered as members of IKPI as many as 542 people (IKPI Surabaya). The number of samples in this study were 84 from the results of calculations using the Slovin formula. The analysis technique used in this research is multiple linear regression. Based on the results of research and hypothesis submission, the following conclusions can be drawn: love of money affects the ethical decisions of tax consultants, locus of control affects the ethical decisions of tax consultants. self efficacy affects the ethical decisions of tax consultants, love of money, locus of control and self efficacy affect the ethical decisions of tax consultants.